Journalistic Practice: Science Storytelling - Angler, Martin W. author. aut Link
XI, 44 p. 1 illus.
Keywords: Science needs to tell good stories to combat fake news and to communicate complex issues. To do this, there are proven techniques, structures, recurring patterns, and elements that no good story should be without. This essential shows why we are wired to respond to stories, how they affect our brains, and the techniques we can use to convey them to every kind of audience, from funders to toddlers. This springer essential is a translation of the original German 1st edition essentials, Journalistische Praxis: Science Storytelling by Angler, Martin W. published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2020. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The Content · Why science needs to tell stories · Story elements · The rule of three · Story formulas from TV, movies, and theater The target groups · Scientists of all disciplines · Journalists, communication scientists The author Martin W. Angler is a freelance science journalist and holds workshops on storytelling techniques, science blogging and social media for scientists and media people. He writes textbooks on science journalism and storytelling. He can be found on Twitter as @martinangler. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.